2018
DOI: 10.1111/coa.13182
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal dysplasia and narrow band imaging: Secondary analysis of published data supports the role in patient follow‐up

Abstract: This study identifies the evidence base for use of NBI in the follow-up for laryngeal dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Hence, a negative finding on NBI would allow monitoring the patient in an outpatient setup, and negate the necessity for unnecessary repeated biopsies, and subsequent worsening of voice quality. 17 Although full thickness biopsies are essential for diagnosis, a recent longitudinal retrospective analysis demonstrated that repeated full-thickness excisions/ biopsies do not confer therapeutic regression of dysplasia in terms of reversal of progression or downgrading of severity, 6 contrary to that previously reported. 18 In fact, the odds of dysplasia worsening had increased by 4% with each additional excision.…”
Section: Treatment Strategiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Hence, a negative finding on NBI would allow monitoring the patient in an outpatient setup, and negate the necessity for unnecessary repeated biopsies, and subsequent worsening of voice quality. 17 Although full thickness biopsies are essential for diagnosis, a recent longitudinal retrospective analysis demonstrated that repeated full-thickness excisions/ biopsies do not confer therapeutic regression of dysplasia in terms of reversal of progression or downgrading of severity, 6 contrary to that previously reported. 18 In fact, the odds of dysplasia worsening had increased by 4% with each additional excision.…”
Section: Treatment Strategiesmentioning
confidence: 92%
“…A recent secondary analysis of preexisting data by Paleri et al has highlighted the benefits and role of NBI on follow-up of patients with laryngeal dysplasia. 17 The treating physician is 4 times less likely to miss a malignant transformation with the use of NBI during follow-up in the case of severe dysplasia. Hence, a negative finding on NBI would allow monitoring the patient in an outpatient setup, and negate the necessity for unnecessary repeated biopsies, and subsequent worsening of voice quality.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Also imaging examination techniques have been tested in attempts to estimate the risks for progression of different types of laryngeal dysplasia. One study using secondary analysis of data from meta-analyses and randomised trials concluded that narrow-band imaging (NBI) is preferred over conventional white light imaging (WLI) and describes the need for NBI in the follow-up of patients with laryngeal dysplasia [ 72 ].…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…However, both prospective and retrospective series clearly demonstrate a benefit in terms of earlier detection of persistence/recurrence (even in the presence of previous microscopically free surgical margins). This is especially true in case of anterior commissure involvement, and apparently normal larynx at fiberoptic evaluation [ 33 , 34 ]. Moreover, an adjunctive advantage of SLM is the possibility to confirm the benign nature of symptomatic granulomas or webs and to promote their prompt surgical management with a functional gain in terms of voice and/or airway patency.…”
Section: Transoral Laser Microsurgerymentioning
confidence: 99%
“…For severe dysplasia, similar post-test probabilities after NBI and WL are 8.0 and 29.7%, respectively. Post-test probabilities in this setting indicate the chance of missing malignancy following NBI or WL in patients who undergo no further intervention [ 34 ].…”
Section: New Technologies In the Follow-upmentioning
confidence: 99%